The Advantages of Virtual Reality in Skill Development Training Based on Project Comparison (2009-2018) - Sunny Thapa Magar; 석혜정 (International Journal of Contents, 2020)
In the era of noble technology, virtual reality (VR) has been adopted in various fields, with the advantages of VR in education being confirmed through numerous studies. In skill development training education, humans or equipment that interact with the trainee are crucial and currently VR is more preferred. In this study, six projects were selected and reviewed in-depth visualizing the use of VR in training and its potential. Comparison between the learning actions of training in the virtual and real environments were conducted. Training through VR is location-dependent, time-dependent, safe, and reversible. VR application is also determined by the preps and feedback-providing functionality which must be emphasized. All the advantages of VR in skill development training make it an opportunity provider. This article can be used by those developing VR projects for skill development training.
Keywords: Skill Development Training; Virtual Reality; Constructivism; Self-learning